PSMA as a Theranostic Target in Hepatocellular Carcinoma: Immunohistochemistry and 68Ga‐PSMA‐11 PET Using Cyclotron‐Produced 68Ga. Issue 5 (15th November 2021) - Thompson, Scott M.; Suman, Garima; Torbenson, Michael S.; Chen, Zong‐Ming E.; Jondal, Danielle E.; Patra, Anurima; Ehman, Eric C.; Andrews, James C.; Fleming, Chad J.; Welch, Brian T.; Kurup, Anil N.; Roberts, Lewis R.; et al.
Abstract : Prostate‐specific membrane antigen (PSMA) is a validated target for molecular diagnostics and targeted radionuclide therapy. Our purpose was to evaluate PSMA expression in hepatocellular carcinoma (HCC), cholangiocarcinoma (CCA), and hepatic adenoma (HCA); investigate the genetic pathways in HCC associated with PSMA expression; and evaluate HCC detection rate with 68 Ga‐PSMA‐11 positron emission tomography (PET). In phase 1, PSMA immunohistochemistry (IHC) on HCC (n = 148), CCA (n = 111), and HCA (n = 78) was scored. In a subset (n = 30), messenger RNA (mRNA) data from the Cancer Genome Atlas HCC RNA sequencing were correlated with PSMA expression. In phase 2, 68 Ga‐PSMA‐11 PET was prospectively performed in patients with treatment‐naïve HCC on a digital PET scanner using cyclotron‐produced 68 Ga. Uptake was graded qualitatively and semi‐quantitatively using standard metrics. On IHC, PSMA expression was significantly higher in HCC compared with CCA and HCA ( P  < 0.0001); 91% of HCCs (n = 134) expressed PSMA, which principally localized to tumor‐associated neovasculature. Higher tumor grade was associated with PSMA expression ( P  = 0.012) but there was no association with tumor size ( P  = 0.14), fibrosis ( P  = 0.35), cirrhosis ( P  = 0.74), hepatitis B virus ( P  = 0.31), or hepatitis C virus ( P  = 0.15). Overall survival tended to be longer in patients without versus with PSMA expression (median overall survival: 4.2 vs. 1.9 years; P  = 0.273). FGF14 (fibroblast growth factor 14) mRNA expression correlated positively (rho = 0.70; P  = 1.70 × 10 ‐5 ) and MAD1L1 (Mitotic spindle assembly checkpoint protein MAD1) correlated negatively with PSMA expression (rho = −0.753; P  = 1.58 × 10 ‐6 ). Of the 190 patients who met the eligibility criteria, 31 patients with 39 HCC lesions completed PET; 64% (n = 25) lesions had pronounced 68 Ga‐PSMA‐11 standardized uptake value: SUVmax (median [range] 9.2 [4.9‐28.4]), SUVmean 4.7 (2.4‐12.7), and tumor‐to‐liver background ratio 2 (1.1‐11). Conclusion: Ex vivo expression of PSMA in neovasculature of HCC translates to marked tumor avidity on 68 Ga‐PSMA‐11 PET, which suggests that PSMA has the potential as a theranostic target in patients with HCC.